Cloud Computing Based Disaster Recovery - Singha, Anjani Kumar; Singla, Anshu; Gupta,, Sudhir Kumar (IJRDO -Journal of Computer Science Engineering, 2016)
Disaster recovery is a persistent problem in IT platforms. This problem is more crucial in cloudcomputing,because Cloud Service Providers (CSPs) have to provide the services to their customers even if the datacenter is down, due to a disaster. In the past few years, researchers have shown interest to disaster recovery using cloudcomputing, and a considerable amount of literature has been published in this area. However, to the best of ourknowledge, there is a lack of precise survey for detailed analysis of cloud-based disaster recovery. To fill this gap,thispaper provides an extensive survey of disaster recovery concepts and research in the cloud environments.We presentdifferent taxonomy of disaster recovery mechanisms, main challenges and proposed solutions. We also describe thecloud-based disaster recovery platforms and identify open issues related to disaster recovery